LA COMUNICACIÓN DEL PATRIMONIO: VALORACIÓN DE LOS PROCESOS COMUNICATIVOS EN MUSEOS DE ASTURIAS - Miguel Ángel SUÁREZ SUÁREZ,Roser CALAF MASACHS,M.ª del Carmen FERNÁNDEZ RUBIO (Fonseca, Journal of Communication, 2023)
Communicating of heritage, especially in museums, is a complex process due to certain particularities. Each museum is unique because of the diversity of objects, the discourses generated and the interactions between different audiences. It makes it difficult to build theories which help to understand and improve the communicative process with-in the museum context. In this way, from prior studies and through both a direct observation and monitoring of the guided visits, this work shows the analysis of 7 museums from Asturias, focusing on the spatial distribution, the museography and the interventions of the teachers and students.